(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This article focuses on a new category of urban spaces, the ‘super-places’, considered as a mix between shopping centres and entertainment parks. Following Walter Benjamin’s studies on urban modernity, the super-places – standing out as utopias or enchanted fortresses in the unsteady and territorialized areas of the contemporary metropolis – will be defined as an evolution of the phantasmagorias where the Parisian flâneur used to stroll. In order to describe the experience of suspension and performance of identity affecting the visitor of the super-places, the concept of ‘hyperreality’, developed by Umberto Eco in his paper Dalla periferia dell’impero (1977), will also be used.